Pengaruh Disiplin Kerja terhadap Kinerja Personel dengan Mempertimbangkan Komitmen Organisasi dan Kepuasan Kerja Studi Empiris di Kompi Bantuan Yonif 753/AVT Korem 173/PVB Kodam XVII/Cenderawasih - Hermawan Budi Santoso; Endah Winarti HS; Mochamad Taufiq (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The objective of this study is to analyze the impact of organizational commitment and job satisfaction on personnel performance, with work discipline as a mediating variable. The study population includes all 115 employees of the Support Company, Yonif 753/AVT Korem 173/PVB Kodam XVII/Cenderawasih, with a sample size of 98 respondents selected using the census method. Data were analyzed using regression analysis and processed with SPSS. The results indicate that organizational commitment and job satisfaction have a positive and significant effect on work discipline. Work discipline also has a positive and significant impact on personnel performance. Furthermore, organizational commitment and job satisfaction positively and significantly influence personnel performance. The Sobel test demonstrates that work discipline can mediate the effects of organizational commitment and job satisfaction on personnel performance